"If You Don't Like it Here, You Can Leave". Issue 11 (November 2015) - Unknown
<x xml:space="preserve">Abstract</x> Company owner Robert Bates called a meeting to discuss the substandard workmanship of a crew. During the meeting, Bates yelled at employee Juan Marana and told him that he was partially to blame for the failures on the assignment.